MODELO DE ALINHAMENTO DOS PROJETOS À ESTRATÉGIA DE NEGÓCIO: ESTUDO DE CASO EM UMA EMPRESA DE GRANDE PORTE - Leite, Darwin Magnus (2010)
The search for prosperity of business in today's business environment has stimulated the continued competition between organizations, which requires the development and implementation of an appropriate business strategy. At the same time, it has been expanded the use of projects for implementation of initiatives from the strategic plans. This paper identifies a model of projects alignment to business strategy in order to understand how the management of projects should be conducted so that its results meet the strategic objectives of a company. To achieve this purpose, it was described in the context of this work approach, formulated specific objectives and issues that meet the general goal of this research. In continuation, it was conducted a descriptive and bibliographic search to establish a review of the literature related to strategy, to project management and strategic alignment, that examines the theoretical structure of these topics and their inter-relationship. To examine theoretical foundations of the relationship between strategy and projects it was made an exploratory research, using a bibliometric study. The literature review and conceptual analysis provided a basis for proposing a theoretical model of projects strategic alignment. In addition, it was made a field research involving a case study in the engineering sector of a large company, employing ex post facto and documentary methods, as well interview and questionnaires techniques. The Management practices observed in the case study were analyzed quantitatively and qualitatively in order to validate the theoretical model of project strategic alignment.